A review on the green and sustainable synthesis of silver nanoparticles and one-dimensional silver nanostructures - Kaabipour, Sina; Hemmati, Shohreh (Beilstein journal of nanotechnology, 2021)
The significance of silver nanostructures has been growing considerably, thanks to their ubiquitous presence in numerous applications, including but not limited to renewable energy, electronics, biosensors, wastewater treatment, medicine, and clinical equipment. The properties of silver nanostructures, such as size, size distribution, and morphology, are strongly dependent on synthesis process conditions such as the process type, equipment type, reagent type, precursor concentration, temperature, process duration, and pH. Physical and chemical methods have been among the most common methods to synthesize silver nanostructures; however, they possess substantial disadvantages and short-comings, especially compared to green synthesis methods. On the contrary, the number of green synthesis techniques has been increasing during the last decade and they have emerged as alternative routes towards facile and effective synthesis of silver nanostructures with different morphologies. In this review, we have initially outlined the most common and popular chemical and physical methodologies and reviewed their advantages and disadvantages. Green synthesis methodologies are then discussed in detail and their advantages over chemical and physical methods have been noted. Recent studies are then reviewed in detail and the effects of essential reaction parameters, such as temperature, pH, precursor, and reagent concentration, on silver nanostructure size and morphology are discussed. Also, green synthesis techniques used for the synthesis of one-dimensional (1D) silver nanostructures have been reviewed, and the potential of alternative green reagents for their synthesis has been discussed. Furthermore, current challenges regarding the green synthesis of 1D silver nanostructures and future direction are outlined. To sum up, we aim to show the real potential of green nanotechnology towards the synthesis of silver nanostructures with various morphologies (especially 1D ones) and the possibility of altering current techniques towards more environmentally friendly, more energy-efficient, less hazardous, simpler, and cheaper procedures.